Are older people more vulnerable to long term impacts of disaster? - Rafiey, Hassan; Momtaz, Yadollah Abolfathi; Alipour, Fardin; Khankeh, Hamidreza; Ahmadi, Shokoufeh; Khoshnami, Mohammad Sabzi; Haron, Sharifah Azizah (Dove Medical Press, 2016)
Background: Despite the growing interest in the study of disasters, there is limited research addressing the elderly population that lead to prejudiced beliefs that older adults are more vulnerable to disasters than younger adults. This study aimed to compare positive mental health between elderly and young earthquake survivors. Method: Data for this study, consisting of 324 earthquake survivors, were obtained from a population-based cross-sectional survey conducted in Iran, 2015. The long-term effect of earthquake was assessed using the Mental Health Continuum-Short Form questionnaire. A one-way multivariate analysis of covariance (MANCOVA) using SPSS (version 22) was used in data analysis. Results: Older adults scored significantly a higher level of overall positive mental health (mean [M]=34.31, standard deviation [SD]=10.52) than younger age group (M=27.48, SD=10.56, t=-4.41; P<0.001). Results of MANCOVA revealed a statistically significant difference between older and young adults on the combined positive mental health subscales (F(3,317)=6.95; P<0.001), after controlling for marital status, sex, and employment status. Conclusion: The present findings showing a higher level of positive mental health among elderly earthquake survivors compared with their younger counterparts in the wake of natural disasters suggest that advancing age per se does not contribute to increasing vulnerability.